EP 46. Accuracy of deep brain stimulation electrodes placement using frameless system – Nexframe©. Issue 9 (September 2016) - Bardon, J.; Krahulik, D.; Nevrly, M.; Otruba, P.; Vaverka, M.; Kanovsky, P.
Abstract : Objective: The aim of the study was to evaluate the placement accuracy of the deep brain stimulation (DBS) electrodes using the frameless navigation NexFrame© in our department. Background: Methods for targeting the subthalamic nucleus (STN) in case of Parkinson disease (PD), ventral intermediate thalamic nucleus (ViM) in case of essential tremor (ET) and globus pallidus internus (GPi) in case of dystonia, differ in using direct visualization of preoperative magnetic resonance scans, in using intraoperative microelectrode recording or in anatomical target coordinates. A frame based stereotaxy or a frameless stereotactic system (NexFrame©) are used during the electrodes placement. Accurate placement of an electrode is necessary for the correct function of the deep brain stimulation. Methods: Coordinates of the planned target point according to anterior and posterior commissural points are found using preoperative MRI of the brain and are usually modified intraoperatively according to microrecording and clinical examination. Coordinates of the real position of the electrode are detected using the fusion of preoperative MRI with postoperative CT. To determine the placement accuracy of the electrodes, the total error and the lateral, anteroposterior and vertical errors were calculated. Results: 64 DBS electrodes were implanted using NexFrame© system to 33 patients diagnosed with PD, ET or dystonia (mean age 61.6 ± 8.7) between 2013 and 2015. The mean total error was 2.38 ± 1.24 mm, the mean lateral error was 1.21 ± 0.80 mm, the mean anteroposterior error was 1.29 ± 0.95 mm and the mean vertical error was 1.17 ± 1.08 mm. All results were compared to the results of other authors' studies. Conclusions: Results of our study show that using the frameless system NexFrame© in our department provides sufficient placement accuracy of electrodes needed for successful treatment using the DBS (Starr et al., 2002; Schrader et al., 2002; Patwardhan et al., 2004; Holloway et al., 2005; Hamid et al., 2005; Fitzpatrick et al., 2005; Kelman et al., 2010 ).